"Aplicación d bioeinsecticidas y químio para controlar insectos-plagas en el cultivo de maní (Arechis hypogaea L.), durante la época en el Cantón Quevedo". - Arias Macías, Galo Paúl (2014)
The property "The María" located in the Canton Mocache, belonging to the State Technical University of Quevedo; it is located in the km 7 of the road Quevedo the Connection, being the situation geographical 79 0 27´ 00´ of longitude West, 01 0 06´ 00 of South latitude and 76 meters on the level of the sea, during the final time of the summer and entrances of winter of the year 2013 - 2014; the current investigation on the bioinsecticidas application and chemist to control insect-plagues in the peanut cultivation, during the time of the summer in the Canton Mocache, had as general objective: To evaluate the action of two bioinsecticidas and a chemist in the control of the main insects plagues, and as specific objectives: To study the morphological behavior of the peanut cultivation, in function to the application of two bioinsecticidas and a chemist. to determine the 2 bioinsecticidas and the chemist of better control in insects plagues and that they present positive answers at production level, to carry out the economic analysis, in function of benefits and costs for hectare......................................